Mesoporous implantable Pt/SrTiO3:C,N nanocuboids delivering enhanced photocatalytic H2-production activity via plasmon-induced interfacial electron transfer - Tamiolakis, Ioannis; Liu, Dong; Xiao, Fangxing; Xie, Jian; Papadas, Ioannis T.; Salim, Teddy; Liu, Bin; Zhang, Qichun; Choulis, Stelios A.; Armatas, Gerasimos S. (My University, 2018)
Band edge engineering of semiconductor nanostructures is one of the most appealing approaches to enhance light absorption, carrier separation and, ultimately, solar to fuel conversion efficiency. In this study, we devise a facile polymer-assisted sol-gel chemical method to prepare highly porous, crystalline implanted SrTiO3 (STO) nanoparticles and demonstrate their performance for photocatalytic hydrogen generation from water. X-ray scattering, electron microscopy, and nitrogen physisorption data corroborate that the as-made catalysts comprise 100-nm-sized nanocuboid particles containing a highly internal porous structure (BET surface area ∼176 m2 g−1) with uniform mesopores (ca. 5.8 nm in diameter). Interestingly, a partial substitution of N and C for O is attained in STO lattice with this synthetic protocol, according to the elemental analysis, and infrared (IR) and X-ray photoelectron spectroscopy (XPS) studies. Compared to STO:C,N, the STO:C,N mesoporous decorated with Pt nanoparticles (ca. 3 nm) present unique attributes that allow for an impressive improvement of up to 74-fold in photocatalytic H2-production activity. By combining UV–vis/NIR optical absorption, photoluminescence, Raman and electrochemical impedance spectroscopy, we show that this improved performance arises from the unique nanostructure, which provides massive surface active sites, and the proper alignment of defect states and conduction band-edge position of the STO:C,N semiconductor with respect to the interband transitions of metal, which permit efficient plasmon-induced interfacial electron transfer between the Pt–STO:C,N junction.
Keywords: Hydrogen production; Mesoporous materials; Nanoparticles; Photocatalysis; Strontium titanate